Guía Para La Ejecución De Una Auditoria De Sistemas A La Plataforma Secop (Sistema Electrónico De Contratación Pública) (2023)
The SECOP, Electronic System for Public Procurement, is an online platform used in Colombia to manage and publish the State's public procurement processes. In order to comply with Law 1712 of 2014, which seeks to regulate the right of access to public information, the procedures for the exercise and guarantee of the right and the exceptions to the publicity of information. For this reason, the publication of contracts in the SECOP is necessary.